Toxic impacts induced by Sodium lauryl sulfate in Mytilus galloprovincialis - Freitas, Rosa (2020)
Pharmaceuticals and personal care products (PPCPs) are continuously dispersed into the environment, as a result of human and veterinary use, reaching aquatic coastal systems and inhabiting organisms. However, information regarding to toxic effects of these compounds towards marine invertebrates is still scarce, especially in what regards to metabolic capacity and oxidative status alterations induced in bivalves after chronic exposure. In the present study, the toxic impacts of Sodium lauryl sulfate (SLS), an anionic surfactant widely used as an emulsifying cleaning agent in household and cosmetics, were evaluated in the mussel Mytilus galloprovincialis, after exposure for 28 days to different concentrations (0.0; 0.5; 1.0; 2.0 and 4.0 mg/L). For this, effects on mussels respitation rate, metabolic capacity and oxidative status were evaluated. The obtained results indicate a significant decrease on mussel's respiration rate after exposure to different SLS concentrations, an alteration that was accompanied by a decrease of bioconcentration factor along the increasing exposure gradient, especially at the highest exposure concentration. Nonetheless, the amount of SLS accumulated in organisms originated alterations in mussel's metabolic performance, with higher metabolic capacity up to 2.0 mg/L followed by a decrease at the highest tested concentration (4.0 mg/L). Mussels exposed to SLS revealed limited antioxidant defense mecanhisms but cellular damage was only observed at the highest exposure concentration (4.0 mg/L). In fact, up to 2.0 mg/L of SLS limited toxic impacts were observed, namely in terms of oxidative stress and redox balance. However, since mussel's respiration rate was greatly affected by the presence of SLS, the present study may highlight the potential threat of SLS towards marine bivalves, limiting their filtration capacity and, thus, affecting their global physiological development (including growth and reproduction) and ultimely their biochemical performance (afecting their defense capacity towards stressful conditons).